Analisis Fonem terhadap Bahasa Slang di Sosial Media Twitter, Instagram dan Facebook - Isnaini Darmawan; Nadhifa Indana Zulfa Rahman (Departement of Mathematics Education, 2023)
The development of the times has had such a big impact on social media in its use. The higher the enthusiasm of social media users, the higher the variety of languages ​​used. Basically, the problem that we want to know is how the form, meaning, and function of slang at the phonological level are compared to standard Indonesian in Twitter, Instagram, and Facebook social media. The scope of the following research is on social media Twitter, Instagram, and Facebook. The research method used is the observation method. Data is concentrated through observation and recording of slang uploaded on social media Twitter, Instagram, and Facebook. The analysis technique is a qualitative descriptive technique to describe, examine and analyze the problems to be studied. The data collected is in the form of seventy slang on social media Twitter, Instagram, and Facebook which have been thoroughly studied so as to obtain conclusions about slang phonemes on Twitter, Instagram, and Facebook social media. On social media Twitter, Instagram, and Facebook there are additions, subtractions, changes in phonemes